The Concept of Citizenship in Afet Inan, Ataturk's Protegee and a Pioneering Woman Historian in the Early Kemalist Era - Daldal, Asli (ALEXANDRU IOAN CUZA UNIV IASI FAC PHILOSOPHY & SOCIAL-POLITICAL SCIENCES, 2022)
Afet Inan is one of the first engagee historians of the early Republican Era who was particularly interested in providing historical bases to Kemalist concepts of history and governance. She was very close to Mustafa Kemal Ataturk and, in that sense, her thoughts and intellectual preferences reflected those of Mustafa Kemal. This essay is particularly interested in Inan's conception of citizenship. As citizenship, State, and history are inseparable, the article also tackles with Kemalist historiography, Kemalist feminism and Turkish thesis of history. The aim is to examine how Inan reinvents the Turkish citizen that would fulfil all the duties necessary to make the nation progress. As a pioneering woman historian of the early Republican era, Inan often emphasized the importance of unity and order within the society, and to reach this internal cohesion she saw the rights and duties of the citizens as outstandingly important. Although far from the progressivist attitudes some earlier feminists adopted in the Republic, Ivan nevertheless provided a theoretical basis for the extension of suffrage to women citizens in the young Kemalist Republic.
Keywords: Kemalist feminism; Afet Inan; Kemalist historiography; Kemalist citizenship; Inan's conception of citizenship; Turkish thesis of history; Arts & Humanities - Other Topics